Early response evaluation during preoperative chemotherapy for colorectal liver metastases: Combined size and morphology‐based criteria predict pathological response and survival after resection. Issue 2 (1st December 2019) - Primavesi, Florian; Fadinger, Nikolaus; Biggel, Simon; Braunwarth, Eva; Gasser, Elisabeth; Sprung, Susanne; Göbel, Georg; Gassner, Eva; Stättner, Stefan; Öfner, Dietmar
Abstract: Background: Short treatment‐duration with early restaging is crucial to avoid liver injury after preoperative chemotherapy (preopCTX) for colorectal liver metastases (CRLM). Response evaluation according to response evaluation criteria in solid tumors (RECIST) criteria implies several limitations. Early tumor shrinkage (ETS; ≥20% size reduction <6‐12 weeks) or morphological criteria (MC) may better predict oncological outcome. Methods: In patients undergoing resection after preopCTX between 2003–2017 pathological and radiological response was reassessed according to Blazer classification, ETS, MC, and RECIST within 90 days and correlated with survival. Results: Seventy‐two patients were included, with a median of two (1‐10) liver lesions, 53% bilobar involvement, and 7% extrahepatic disease. PreopCTX was applied for 3 months in median (1‐6). During restaging after a median of 62 days, presence of ETS was associated with improved median overall survival (OS; 57.1 vs 33.7 months; P = .010) and disease‐free survival (16 vs 7.2 months; P = .025). MC significantly correlated with major pathological response ( P = .021). When combining ETS with optimal MC, presence of one or both factors was associated with pathological response (61.5% and 92.3%; P = .044) and OS in log‐rank ( P = .011), and multivariable analysis (hazard ratio [HR] 0.41; 95% confidence interval [CI], 0.19‐0.90 and HR 0.32; 95%CI, 0.11‐0.97). Conclusion: Response‐grading by combined ETS/MC criteria less than 90 days after preopCTX initiation predicts pathological response and postoperative survival in CRLM.